The contribution of professions to the governance of integrated care: Towards a conceptual framework based on case studies from Denmark. Issue 2 (April 2022) - Burau, Viola; Kuhlmann, Ellen; Ledderer, Loni
Objective: Good governance of integrated care is key to better health care, but we know little about how professions can help make this happen. Our aim is to introduce a conceptual framework to analyse how professions contribute to the governance of integrated care, and to apply the framework to a secondary analysis of selected case studies from Denmark. Methods: We developed a framework, which identified the what, how and why of the contribution professions make to the governance of integrated care. We included five qualitative Danish studies, using coordination as an indicator of integrated care. We adopted a thematic approach in our analysis, combining deductive and inductive elements. Results: Health professions engage in highly diverse activities, which fall into closely connected clusters of more formal or more informal coordination. Professions apply many different adaptive mechanisms at different levels to fit coordination into local contexts. Professions are driven by interlocking rationales, where a common focus on patients connects organizational and professional concerns. Conclusions: Our analytical framework emerges as a useful tool for analysis. The contribution of professions to the governance of integrated care needs greater attention in health policy implementation as it can promote more effective governance of integrated care.